Three new species of Dysponetus Levinsen, 1879 (Polychaeta: Chrysopetalidae) from the South Atlantic and Southern Ocean, with a re-description of Dysponetus bulbosus Hartmann-Schröder, 1982 - Darbyshire, Teresa; Brewin, Paul E. (Zootaxa, 2015)
Three new species of Dysponetus (Polychaeta: Chrysopetalidae) are described from the South Atlantic and Southern Ocean: Dysponetus ovalisetosus n. sp. from the Falkland Islands, Dysponetus bricklei n. sp. from South Georgia and Dysponetus antarcticus n. sp. from Antarctica are all characterized by having notochaetae that are oval in cross-section in contrast to the D-shape described for seven of the other species of Dysponetus. Dysponetus antarcticus n. sp. is the most distinct due to the combination of both a ventral cirrus on segment 3 and four eyes. Formerly mis-identified as Dysponetus bulbosus Hartmann-Schröder, 1982, it was discovered while clarifying the contradictory descriptions of that species published by Hartmann-Schröder in 1982 and 1986. Dysponetus bulbosus is re-described and newly figured. Dysponetus bricklei n. sp. and Dysponetus ovalisetosus n. sp. can be determined by comparing several characters including position of the median antenna, shape of the palps and cirri, and the number and shape of both the noto- and neurochaetae.